Avaliação da atividade antinociceptiva e anti-Inflamatória do óleo essencial de Lippia pedunculosa - Braga , Renan Marinho (2016)
Pain is a relevant homeostasis element, its main role is to warn about stimuli that can cause tissue damage, allowing that defense or escape mechanisms are adopted. Although numerous substances and progress in the development of pain control therapy, there is still an urgent need for potent analgesics with fewer adverse effects. An alternative are natural products, among these, essential oils stand out, which have different pharmacological effects deriving from the chemical and structural variability of their compounds. The essential oil of Lippia pedunculosa (EOLP), has trypanocide and amebicide effect already reported in the literature, however its action in experimental models of analgesia and inflammation in mice, has not been studied. In the behavioral pharmacological screening, the different doses tested 200, 300, 400 and 750 mg/kg (p.o.) showed psycho depressor behavioral changes such as decreased ambulation, analgesia, ptosis and loss of ear reflex. No deaths were scored. To the subsequent experiments, doses of 200, 300 and 400 mg/kg (p.o.), were chosen. In the open field test it was found that EOLP has a psycho depressor drug profile, because parameters such as ambulation and rearing of animals were significantly decreased. It was confirmed by the rota-rod test, that animals treated with EOLP had no changes in motor coordination, discarding a possible myorelaxant or neurotoxic effect. Following with the models to evaluate the antinociceptive activity, in the writhing-induced by acetic acid test, EOLP was effective, reducing the number of contortions. It also reduces the time licking in both phases of the formalin test, but was not able to increase the latency to thermal stimulus perception in the hot plate test. However, the EOLP analgesic effect was not reversed by naloxone suggesting that it acts by non-opioids pathways. Finally, the model of carrageenan-induced peritonitis, the EOLP decreased the leukocytes migration in the peritoneal fluid. Thus, these results show that EOLP has antinociceptive and anti-inflammatory effect by yet unknown pathways.